Engineering materials V : selected, peer reviewed papers from the 5th Cross-strait Workshop on the Engineering Materials (CSWEM 5), held in I-Shou University, Taiwan on November 19-20, 2010 - Chen, Chin-Yi; Chang, Jing-Tang (Key engineering materials ;, 2011)
This special collection integrates fundamental and applied research work which focused on various fields of engineering materials use. The contents are organized under various technical headings in order to address experimental, theoretical and manufacturing issues associated with the development of new metallic materials and processes, advanced electronic packaging, solar cells and nano-materials, and the evolving approaches used in commercial applications. The contents suggest a wealth of new ideas.